Análisis de la medición como Item básico de la estructura de los modelos contables (2011)
The measurement necessity of characteristics and present objects in all type of realities has shown the preoccupation of many areas of knowledge to determine every day higher quality levels in the measurement with the minimum of permissible errors. This preoccupation is also in accounting and it is shown in this case, in the formulation of the components or basic items of the countable models: criteria of recognition, measurement methods and capital concepts